17th International IEEE Conference on Intelligent Transportation Systems (ITSC) 2014
DOI: 10.1109/itsc.2014.6958092
|View full text |Cite
|
Sign up to set email alerts
|

Traffic routing in urban environments: The impact of partial information

Abstract: Abstract-There are many studies concerning the problem of traffic congestion in cities. One of the best accepted solutions to relieving congestion involves optimization of resources already available, by means of balancing traffic flows to minimize travel delays. To achieve this optimization, it is necessary to collect and process Floating Car Data (FCD) from vehicles. In this paper we evaluate the repercussions of partial information on the overall traffic view, and consequently on the outcome of the optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…After reviewing previous works, we observed that one of the most used scenarios to evaluate proposals is the scenario known as Manhattan (or grid type) [25][26][27]. In our case, two synthetic networks were designed based on the Manhattan scheme: one of the 4 × 4 (M4) and another 5 × 5 (M5).…”
Section: Test Scenariomentioning
confidence: 99%
“…After reviewing previous works, we observed that one of the most used scenarios to evaluate proposals is the scenario known as Manhattan (or grid type) [25][26][27]. In our case, two synthetic networks were designed based on the Manhattan scheme: one of the 4 × 4 (M4) and another 5 × 5 (M5).…”
Section: Test Scenariomentioning
confidence: 99%
“…In [5], the authors use partial knowledge of the network learned by users in a centralized context -a server receives voice tweets from drivers on traffic events. In [6], they quantify the impact of partially-available information on the computation of route optimization.…”
Section: Related Workmentioning
confidence: 99%